Cannabis concentrate vaping chemistry - Kaelas R. Munger; Killian M. Anreise; Robert M. Strongin (Frontiers in Toxicology)
BackgroundThis review article addresses the vaping chemistry of manufactured cannabis concentrates—a topic that remains under-researched despite the widespread availability and growing popularity of these products. Given their current prevalence and the fact that many of the findings discussed herein are from early-stage investigations, further research is essential to fully assess the public health risks associated with concentrate use. The purpose of this article is to help begin to bridge this knowledge gap by outlining the technical challenges of studying cannabis concentrates and to present evidence-based data concerning toxicant exposures as a foundation for future investigations.MethodsA search of cannabis concentrate vaping within the date range of 2019-2025 on Google Scholar returned approximately 2,700 hits. A cannabis concentrate was defined as a sample containing at least 50% (w/w) cannabinoids. In addition to our group’s articles, the search results contained six manuscripts that described at least a partial focus on molecular emissions specifically derived from vaping or dabbing samples that included cannabis concentrates.FindingsStudying cannabis concentrate vaping poses distinct technical challenges that differ from those associated with electronic nicotine delivery systems. Emissions from vaping concentrates contain a substantial proportion of harmful aerosol toxicants, including isoprene, 3-methylcrotonaldehyde, 3-methyl-1-butene, and 2-methyl-2-butene. Moreover, some concentrate formulations have contained hazardous additives such as pine rosin and ketene precursors such as cannabinoid acetates. As with nicotine vaping, the presence of oxygen plays a critical role in driving the formation of many toxic chemical degradation products during vaping.ConclusionSince the legalization of recreational cannabis, concentrates have become one of the most rapidly expanding segments of the U.S. cannabis market. However, research into the specific health risks of vaping these products has significantly lagged their widespread use. The studies presented in this review article highlight the potential for exposure to known toxicants during the vaping of cannabis concentrates.